Analisis Potensi Biomassa Limbah Pabrik Kelapa Sawit (PKS) Untuk Pembangkitan Energi Listrik Di Kabupaten Landak Provinsi KalimantanBarat - Simanjuntak, Yohannes M; Danial, D .; Taufiqurrahman, M .; Kurniawan, Eddy . (ELKHA : Jurnal Teknik Elektro, 2016)
Abstract– The potency of palm oil mills (PKS) biomass in Kabupaten Landak have been evaluated as alternative for electrical energy in that area. The results have shown that solid biomass (empty fruit bunchs and shells) produced by those of PKS in 2016 have significant potency for generating electrical power. By using steam turbine technology, the biomass potency equal to 2 units of 13 MW power plant. Keywords–Biomass, empty fruit bunch, shell, alternative energy, Landak